Novel Functions of ErbB4 and NRG-1 in Development and Cancer - Paatero, Ilkka (Annales Universitatis Turkuensis D 1060, 2013)
Cells communicate, or signal, with each other constantly to ensure proper functioning of tissues and organs. Cell signaling is often performed by interplay of receptors and ligands that bind these receptors. ErbB receptors (epidermal growth factor receptors, EGFR, HER) bind extracellular growth factors and transduce these signals inside of cells. ErbB dysfunction promotes carcinogenesis, and also results in numerous defects during normal development. This study focused on the functions of one member of the ErbB receptor family, ErbB4, and growth factor, neuregulin-1 (NRG-1), that can bind and activate ErbB4. This study aimed to find novel functions of ErbB4 and NRG-1. Hypoxia, or deficiency of oxygen, is common in cancer and ischemic conditions. One of the key findings of the work was the identification and characterization of a cross-talk between ErbB4 and Hypoxia-inducible factor 1α (HIF-1α), the central mediator of hypoxia signaling. ErbB4 activation by NRG-1 was found to increase HIF-1α activity. Interestingly, this regulation occurred in reciprocal manner as HIF-1α was also able to increase protein levels of NRG-1 and ErbB4. Moreover, expression of NRG-1 and ErbB4 was associated with HIF activity in vivo in human clinical samples and in mice. Reduction of functional ErbB4 in developing zebrafish embryos resulted in defects in development of the skeletal muscles. To study ErbB4 functions in pathological situation in humans, clinical samples of serous ovarian carcinoma were analyzed using tissue microarrays and real-time RT-PCR. A specific isoform of ErbB4, CYT-1, was associated with poor survival in serous ovarian cancer and increased anchorage independent growth of ovarian cancer cells in vitro. These observations demonstrate that ErbB4 and NRG-1 are essential regulators of cellular response to hypoxia, of development, and of ovarian carcinogenesis.

Elimistön solut viestivät keskenään normaalin kehityksen ja aikuisten kudosten normaalin toiminnan aikana. Tämä viestintä varmistaa solujen ympäristöönsä soveltuvan toiminnan. Soluviestintää välittävät reseptorit ja niihin sitoutuvat ligandit. ErbB (epidermaalisen kasvutekijän reseptorit, EGFR, HER) reseptorit sitovat solunulkoisia kasvutekijöitä, ja välittävät viestin solun sisälle. Monissa syövissä ErbB reseptorien toiminnan säätely on häiriintynyt. Tämä tutkimus keskittyi erään ErbB reseptorin, ErbB4:n, ja sen ligandin NRG-1:n toimintaan. Tutkimuksen päämääränä oli löytää uusia ErbB4:n ja NRG-1:n säätelemiä prosesseja ja niiden toimintamekanismeja. Hapenpuutetta, hypoksiaa, esiintyy monissa syövissä ja iskeemisissä tautitiloissa. Tutkimuksessa löytyi yhteys ErbB4:n välittämän viestinnän ja kes¬keisen hapen vähyyden viestijän (hypoksian indusoima tekijä 1α, HIF-1α) välillä. NRG-1 ja ErbB4 lisäsivät HIF-1α:n määrää ja aktiivisuutta. Tämä vuorovaikutus oli molemminpuolis¬ta, sillä myös HIF-1α:n aktiivisuus johti lisääntyneeseen NRG-1- ja ErbB4-määrään. Lisäksi lisääntynyt HIF-aktiivisuus oli yhteydessä lisääntyneeseen ErbB4:n ja NRG-1:n määrään kliinisissä näytteissä ja hiirimalleissa. ErbB4:n toiminnan estäminen seeprakalan alkiois¬sa johti luurankolihasten kehityksen häiriöihin. ErbB4:n toiminnan tutkimiseksi ihmisissä analysoitiin seröösin munasarjasyövän potilasnäytteitä kudossiruja sekä reaaliaikaista RT-PCR:ää käyttäen. ErbB4:n erityisen CYT-1 isomuodon ilmentyminen oli yhteydessä huonoon ennusteeseen seröösissä munasarjasyövässä sekä lisäsi munasarjasyöpäsolujen kasvua in vitro. Tutkimuksessa tehdyt havainnot viittaavat siihen, että NRG-1 ja ErbB4 ovat tärkeitä säätelijöitä solujen reagoimisessa hapenpuutteseen, kudosten kehittymisessä sekä seröösissä munasarjasyövässä.